Metabolic tumor cell adaptation: tyrosine phosphorylation modulates cell surface expression of NKCC2 and KCC3 - Loureiro, Cláudia (2020)
Introduction: Tumor cells require cellular chloride and potassium transport to adapt to a changing microenvironment, both for cell volume regulation and membrane potential maintenance. Cellular chloride and potassium entry or exit are mediated at the plasma membrane by cotransporter proteins of the solute carrier 12 family. For example, NKCC2 resorbs chloride with sodium and potassium ions at the apical membrane of epithelial cells in the kidney, whereas KCC3 releases chloride with potassium ions at the basolateral membrane. Their ion transport activity is regulated by protein phosphorylation in response to signaling pathways. An additional regulatory mechanism concerns the amount of cotransporter molecules inserted into the plasma membrane. Material and Methods: Cotransporter constructs were transfected into HEK293 cells and the activity of spleen tyrosine kinase (SYK) modulated by incubation with SYK inhibitors or by co-transfection with siRNAs, kinase-dead, or constitutively active SYK mutants. Cotransporter abundance in the plasma membrane was analyzed by biotinylation of cell surface proteins. Results and Discussions: Here we describe that tyrosine phosphorylation of NKCC2 and KCC3 regulates their plasma membrane expression levels. We identified that SYK phosphorylates a specific N-terminal tyrosine residue in each cotransporter. Experimental depletion of endogenous SYK or pharmacological inhibition of its kinase activity increased the abundance of NKCC2 at the plasma membrane of human embryonic kidney cells. In contrast, overexpression of a constitutively active SYK mutant decreased NKCC2 membrane abundance. Intriguingly, the same experimental approaches revealed the opposite effect on KCC3 abundance at the plasma membrane, compatible with the known antagonistic roles of NKCC and KCC cotransporters in cell volume regulation. Conclusion: We identified a novel pathway modulating the cell surface expression of NKCC2 and KCC3 and show that this same pathway has opposite functional outcomes for these two cotransporters. The findings add knowledge on how tumor cells may respond to microenvironmental changes that affect their cell volume or metabolic crosstalk.